PENGARUH KOMPENSASI, IKLIM ORGANISASI, DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. EZRA BERKAT ANUGRAH MEDAN - Simangunsong, Elisabeth; GS, Romi Andreas; Purba, Imelda R.; Bangun, Kristina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
This study aims to determine the effect of compensation, organizational climate and training on employee performance at PT.Erza Berkat Anugrah Medan with a population of 38 employees and a sample of 32 employees. Data collection was carried out through questionnaires, documentation and interviews. The research method used is quantitative. Data analysis in this study used SPSS version 23.00. The results of t show that in terms of compensation, organizational climate and training have a positive and significant partial effect on employee performance. The F test shows that simultaneously the effect of compensation, organizational climate and training on performance has a significant effect on employee performance. The coefficient of determination is 0.607, meaning that employee performance can be explained by the influence of compensation, organizational climate and training on performance by 60.7%, while the other 39.3% is explained by other variables not included in this study.